Strategy-proof voting for multiple public goods - Alexander Reffgen; Lars-Gunnar Svensson (Theoretical Economics, 2012)
In a voting model where the set of feasible alternatives is a subset of a product set A = A_1×……A_m of m finite categories, we characterize the set of all strategy-proof social choice functions for three different types of preference domains over A, namely for the domains of additive, completely separable, and weakly separable preferences over A.
Keywords: D71; 330; Multiple public goods; strategy-proofness; voting under constraints; additive preferences; separable preferences